2012
DOI: 10.1530/joe-12-0009
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxing effects of estetrol in rat arteries

Abstract: This study compared ex vivo relaxing responses to the naturally occurring human hormone estetrol (E 4 ) vs 17b-estradiol (E 2 ) in eight different vascular beds. Arteries were mounted in a myograph, contracted with either phenylephrine or serotonin, and cumulative concentrationresponse curves (CRCs) to E 4 and E 2 (0 . 1-100 mmol/l) were constructed. In all arteries tested, E 4 had lower potency than E 2 , although the differential effect was less in larger than smaller arteries. In uterine arteries, the nonse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
(37 reference statements)
1
9
0
1
Order By: Relevance
“…It was proved that E2 and P4 had a vasorelaxant action through a non-genomic pathway. Studies on rat arterial beds showed that E2 induced vascular relaxation [17]. The same results were found on the arterial tissues in human [18,19] lamb [20], monkey [21] and mice [12].…”
Section: Discussionsupporting
confidence: 71%
“…It was proved that E2 and P4 had a vasorelaxant action through a non-genomic pathway. Studies on rat arterial beds showed that E2 induced vascular relaxation [17]. The same results were found on the arterial tissues in human [18,19] lamb [20], monkey [21] and mice [12].…”
Section: Discussionsupporting
confidence: 71%
“…IKs and SKs are also expressed in VSMCs of uterine and placental chorionic plate arteries in addition to their expression in ECs [90, 107]. In the uteroplacental system, IKs and SKs participated in the regulation of contractility of uterine and placental vessels [90, 107, 109]. Moreover, SK3 was also involved in regulating uterine vascular remodeling and placental vascularization [110, 111].…”
Section: E2β Signaling and Uteroplacental Circulation In Physiologmentioning
confidence: 99%
“…3 Discovered by Diczfalusy in 1965, 4 the precise effects of E 4 on various tissues during pregnancy remain unknown. A series of recent studies elucidated various tissue-specific properties of E 4 including differential effects on brain, 5 the vascular nitrous oxide system, 6 and membrane actions as opposed to nuclear. 7 Estetrol was identified as a potential drug for human use by Coelingh Bennink in 2001.…”
Section: Introductionmentioning
confidence: 99%